Spatio-Temporal Distribution of Aedes aegypti (Diptera: Culicidae) Mitochondrial Lineages in Cities with Distinct Dengue Incidence Rates Suggests Complex Population Dynamics of the Dengue Vector in Colombia (2015)
ABSTRACT: Knowledge on the population structure of Aedes aegypti, the main vector of the dengue virus (DENV), is essential to improving dengue fever prevention strategies in endemic countries. In Colombia, despite the epidemiological relevance of dengue fever, the genetic population structure and phylogeography of the vector Ae. aegypti is little known. In this study, we evaluated the spatio-temporal structure and phylogeography of Colombian Ae. aegypti populations from cities showing different eco-epidemiologic attributes related to dengue fever. Our results indicated that Colombian Ae. aegypti populations harbor two mitochondrial lineages related to West and East African ancestors. The lineage related to West African populations is the most frequent and widely distributed in Colombia, and it was found in cities with a high incidence of the dengue fever. A second lineage related to East African populations, which may have been recently introduced in some regions, was found in cities showing a low incidence of dengue. These findings suggest complex population dynamic is involved in dengue fever epidemiology in Colombia, and indicate further studies about biological attributes of the Ae. aegypti lineages should be performed.